The Relationship between Motor Skills and Physical Activity Patterns of Students with Disabilities in Special Schools - Mumin, Cep; Nurudin, Ahmad Alwi; Saleh, Muhammad (Journal Coaching Education Sports, 2024)
The research employs a quantitative descriptive method with a correlational design, involving 20 students (15 boys and 5 girls) from SLB Negeri Mutiara Bahari Mandiri, Sukabumi, selected through purposive sampling. Data collection utilized the Movement Assessment Battery for Children Second-editions (MABC-2) to measure motor skills and the Physical Activity Questionnaire for Children (PAQ-C) to assess physical activity levels. Results revealed an average motor skill score of 54.85, classified as "difficulty performing motor tasks," and an average physical activity score of 2, categorized as "low activity." Correlation analysis using Spearman's correlation demonstrated a significant positive relationship (r = 0.661, p = 0.002) between motor skills and physical activity. The findings highlight that students with better motor skills are more likely to engage in physical activities and vice versa. However, many students with intellectual disabilities face challenges in performing motor tasks, particularly those requiring hand-eye coordination, such as catching or bouncing a ball. The lack of stimulation, attention, and adequate facilities also contributes to low physical activity levels, with students often preferring sedentary activities like watching television or playing online games. This study underscores the importance of increasing motor skills and physical activity through collaborative efforts by schools, teachers, parents, and the community. Providing adequate facilities, engaging activities, and continuous encouragement can foster active participation and improve motor skill development in children with intellectual disabilities. These findings offer valuable insights for educators and policymakers in developing inclusive physical education programs tailored to the needs of children with special needs.